ERP-Based Redesign of Inbound Supply Chain Processes in a Indonesian Multiunit SME - Nathanael, William; Okdinawati, Liane; Terminanto, Agung (PT. EQUATOR SINAR AKADEMIA, 2025)
This study aims to examine how business process reengineering accompanied by the implementation of an ERP system (Odoo) can improve the efficiency and accuracy of internal processes in a multi-unit SME in Indonesia. The background to this study is the challenges of cross-unit business coordination, manual process inefficiencies, and lack of data visibility that impact internal supply chain performance. This research employs a qualitative approach through in-depth interviews and field observations, verified through business process modeling and simulation using Bizagi Modeler.The research findings indicate that the business processes prior to the redesign, with ERP implementation, were characterized by fragmented coordination of raw materials, slow approval processes due to manual procedures, and inaccurate data recording. Projected results indicate that process time can be reduced by up to 75%, inventory discrepancies can be reduced by 15% to 3-5%, and cross-unit miscommunication can be significantly reduced. Simulation results using Bizagi show that the total number of lots that can be produced over 60 days increases from 980 to 991 lots. The average time for internal production can be reduced from 3 days and 5 hours to 2 days and 17 hours as recording accuracy improves through the ERP system. These findings emphasize the importance of in-depth process analysis, top management commitment, and structured change management strategies for the successful implementation of ERP systems.